Using Pomegranate Peel and Date Pit Activated Carbon for the Removal of Cadmium and Lead Ions from Aqueous Solution - Wedad A. Al-Onazi; Mohamed H.H. Ali; Tahani Al-Garni (Journal of Chemistry)
Some agricultural byproducts are useful for solving wastewater pollution problems. These byproducts are of low cost and are effective and ecofriendly. The study aim was to investigate the possibility of using pomegranate peel (PP) and date pit (DP) activated carbon (PPAC and DPAC, respectively) as sorbents to remove Cd(II) and Pb(II) from aqueous solutions. Agricultural wastes of DPs and PPs were subjected to carbonization and chemical activation with H3PO4 (60%) and ZnCl2 and used as adsorbents to remove Cd(II) and Pb(II) from their aqueous solutions. The physical characterizations of PPAC and DPAC, including determination of surface area, scanning electron microscopy, energy-dispersive X-ray spectroscopy, and Fourier-transform infrared spectroscopy, were performed. The following factors affected adsorption: solution pH, adsorbent dosage, initial metal ion concentration, and contact time. These factors were studied to identify the optimal adsorption conditions. The results showed that the maximum adsorptions of Cd(II) and Pb(II) were achieved at pH ranging from 6 to 6.5, 90 min contact time, and 0.5 g/L for PPAC and 1 g/L for DPAC dosage. Furthermore, the adsorption efficiencies for both Pb(II) and Cd(II) were higher for PPAC than for DPAC. However, the recorded Qmax values for PPAC were 68.6 and 53.8 mg/g for Pb(II) and Cd(II) and for DPAC were 34.18 and 32.90 mg/g for Pb(II) and Cd(II), respectively. The Langmuir isotherm model fit the adsorption data better than the Freundlich model. Kinetically, the adsorption reaction followed a pseudo-second-order reaction model, with qe ranging from 12.0 to 22.37 mg/g and an R2 value of 0.99.